2022
DOI: 10.1093/oncolo/oyac029
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on Management of Patients with Metastatic Pancreatic Ductal Adenocarcinoma in the United States

Abstract: Background The purpose of this study was to understand how the COVID-19 pandemic has affected health care patterns and outcomes for patients diagnosed with metastatic pancreatic ductal adenocarcinoma (mPDAC) in 2020 compared with those diagnosed with mPDAC in 2019. Patients and Methods We used the Flatiron Health database to identify adults diagnosed with mPDAC from March 1 to September 30, 2019 (pre-COVID-19 cohort) and Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 13 publications
(15 reference statements)
4
18
0
Order By: Relevance
“…In real terms, this represented a 4-month reduction in median survival 3. Our findings are validated by a North American study, which found an increased proportion of patients presenting at later stages and a reduction of 2 months in overall survival in those diagnosed with metastatic PDAC during the pandemic compared with before the pandemic 4…”
supporting
confidence: 76%
See 1 more Smart Citation
“…In real terms, this represented a 4-month reduction in median survival 3. Our findings are validated by a North American study, which found an increased proportion of patients presenting at later stages and a reduction of 2 months in overall survival in those diagnosed with metastatic PDAC during the pandemic compared with before the pandemic 4…”
supporting
confidence: 76%
“…Surgical resection offers the only possibility of a cure in PDAC,9 but is only appropriate in early-stage disease. Therefore, any delays in diagnosis risk restriction of treatment options and a reduction in overall survival 3,4. This is supported by the evidence showing that referral pathways and treatment regimens have changed during the pandemic 3-7…”
mentioning
confidence: 96%
“…In the present study, the absence of survival deterioration in the pandemic cohort as compared with the pre-pandemic cohort seems to be at odds with previous studies that have described an increased mortality among lung cancer patients during the COVID-19 pandemic [ 15 , 16 ]. In other population-based studies of patients with pancreatic, esophageal or colorectal cancers, survival was reportedly worse in the pandemic than the pre-pandemic period [ 17 , 18 ]. Nevertheless, it should be observed that not all patients in the pandemic cohort in our study were infected with SARS-CoV2.…”
Section: Discussionmentioning
confidence: 99%
“…Considering a case fatality rate of approximately 22%, it can be estimated that fewer than 70 deaths were directly attributable to the virus [ 19 ], constituting a small fraction of the overall 935 deaths in this study. Furthermore, in our study, unlike some previous population-based studies [ 17 , 18 ], we included only the patients who successfully managed to receive their cancer treatment; therefore, we did not consider the excess mortality due to unavailable cancer treatment during the pandemic. While these observations may help explain the absence of survival deterioration among the pandemic cohort in our study, they do not explain the improvement in survival during the pandemic among patients with lower PD-L1 expression treated with pembrolizumab monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“… 1 Paluri et al recently reported that over 60% of patients diagnosed with pancreatic ductal adenocarcinoma (PDAC), the most common form of pancreatic cancer, were diagnosed with incurable metastatic disease and that this number has increased to nearly 70% during the COVID-19 pandemic. 2 As many patients diagnosed with metastatic PDAC are too unwell to be treated with systemic therapy, 3 the average patient survival is approximately 2–3 months. 4 …”
Section: Introductionmentioning
confidence: 99%